2017
DOI: 10.1149/2.1551712jes
|View full text |Cite
|
Sign up to set email alerts
|

Hysteretic Phenomena between Charging and Discharging in LiNi0.5Mn1.5O4-σ

Abstract: Clarification of the mechanism of hysteretic phenomena between charging and discharging in LiNi 0.5 Mn 1.5 O 4-σ under a closedcircuit voltage is crucial for achieving a high energy efficiency. We performed in situ X-ray diffraction to understand the relationship between the overpotential and the kinetically preferred state of LiNi 0.5 Mn 1.5 O 4-σ during charging and discharging. Very different crystal structures were observed for the cathode during charging and discharging, especially in the low state-of-cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…The trends observed are qualitatively in agreement with many previous reports of in situ XRD on LMNO. 18,27,29,32,43 These changes are roughly symmetrical upon discharge, with a small hysteresis detected in the peak position.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…The trends observed are qualitatively in agreement with many previous reports of in situ XRD on LMNO. 18,27,29,32,43 These changes are roughly symmetrical upon discharge, with a small hysteresis detected in the peak position.…”
Section: Resultsmentioning
confidence: 88%
“…18 However, several in situ diffraction studies on LMNO do not observe any untransformed phases, despite having a detection limit sufficient to observe them. 21,29,32 These contradictory results may be attributed to differences in the crystal morphology, crystal quality, crystallite size, pre-cycling, and charging rate of the LMNO used in each study, which lead to substantial differences in solid state reactivity. 46 One of the possible explanations is that some small fraction of LMNO crystallites experience strong heterogeneity in lithiation, with large barriers to phase transitions.…”
Section: Incomplete Delithiationmentioning
confidence: 99%
See 1 more Smart Citation
“…One major objective is to understand and maximize the solid-solution behavior between these three states during operation, since sharp phase segregation is well-known to slow down kinetics and accelerate degradation. , Significant variations in the competition of the solid-solution vs phase segregation mechanisms during both phase transitions have been reported by many groups. This has led to contradictory mechanisms being proposed including single-phase, , two-phase, ,, and even three phase , coexistence inside individual crystals. The relatively flat voltage curve of LMNO places all of these states very close in energy, which makes experimentally probing the phase diagram difficult.…”
mentioning
confidence: 99%
“…Many groups have repeatedly noted the difficulty of extracting more than around 90% of the Li ions from spinel active materials based on electrochemical and Li stoichiometry measurements. ,,,, In an extreme case, Kan et al showed that a carefully annealed LMNO had dramatically lowered capacity, where less than 20% of the Li was capable of being extracted in the first cycle, and with the capacity gradually increasing on subsequent cycles . However, several in situ diffraction studies on LMNO do not observe any untransformed phases, despite having a detection limit sufficient to observe them. ,, These contradictory results may be attributed to differences in the crystal morphology, crystal quality, crystallite size, precycling, and charging rate of the LMNO used in each study, which lead to substantial differences in solid state reactivity …”
mentioning
confidence: 99%